Comparison of the reproductive performance of the Kacang goats on three synchronization methods - Yendraliza Yendraliza; Rahmi Febriyanti; Muhamad Rodiallah (Universitas Sebelas Maret, 2020)
Objective: This study was conducted to investigate the effect of different methods synchronized on the reproductive performance of the Kacang Goats, estrus response, pregnancy rate, kidding rate, twins and litter size.Methods: Forty-five dam of Kacang goats were divided into three groups (n= 15); 1) goats were injected 1 ml PGF2α (LutalyseTM) on day 1st and after days 11nd. 2) goats have injected 1 ml of GnRH (FertagylTM) on day 1st and the 7th day was injected 1 ml of PGF2α. 3) goats have received 1 ml progesterone (Progesterone-C) on the first day and the 7th day was injected with 1 ml PGF2α. Estrus observations were made on the 12th day for the first group, 8th day for the second group and 8th day for the third group. This data analyzed with a t-test. The effects were considered to be significant when the level of probability was less than 5%.Results: The results showed that visualization estrus (goods), the percentage of estrus (100%), the onset of estrus (51.6 h- 52.6 h), the percentage of pregnancy (100%), birth percentage of kids (100%) Kacang goats better on the use of double PGF2α and a combination of GnRH and PGF2α than the use combination progesterone with PGF2α but the duration of estrus, twins and the kidding rate no difference between treatments.Conclusions: Synchronization method using a combination of GnRH with PGF2α and double PGF2α produces estrus responses, pregnancy rate and birth rates that are higher than the combination Progesterone with PGF2α synchronization method.